2023
DOI: 10.1212/wnl.0000000000207445
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Embolic Source and Outcome in Central Retinal Artery Occlusion

Abstract: Objectives:The etiology of central retinal artery occlusion (CRAO) is unclear in about 50% of patients, suggesting pathomechanical heterogeneity; moreover, little is known about outcomes according to etiology. This study investigated whether the presence of an embolic source affects outcome in CRAO.Methods:CRAO patients within 7 days of symptom onset were retrospectively enrolled. Clinical parameters, including initial and 1-month visual acuity, CRAO subtype, and brain images, were reviewed. CRAO etiology was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The primary causes of CRAO are cardioembolisms and artery-to-artery embolisms of the carotid artery; however, approximately half of all CRAO cases are due to an unknown aetiology, which is much higher than the proportion of stroke cases with unknown causes. 17 Differences in cerebrovascular and cardiovascular factors between patients with recurrence in the same eye and those with recurrence in the opposite eye may suggest variations in the thromboembolic risk associated with recurrent RAO. 18 19 This implies that although the patients did not have any obvious cerebrovascular abnormalities, and had a low likelihood of systemic vascular disease, there was still a possibility of RAO recurrence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The primary causes of CRAO are cardioembolisms and artery-to-artery embolisms of the carotid artery; however, approximately half of all CRAO cases are due to an unknown aetiology, which is much higher than the proportion of stroke cases with unknown causes. 17 Differences in cerebrovascular and cardiovascular factors between patients with recurrence in the same eye and those with recurrence in the opposite eye may suggest variations in the thromboembolic risk associated with recurrent RAO. 18 19 This implies that although the patients did not have any obvious cerebrovascular abnormalities, and had a low likelihood of systemic vascular disease, there was still a possibility of RAO recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the association between RAO and embolic sources from the heart, 17 it is crucial to perform cardiac evaluations, such as coronary angiography and transthoracic echocardiography, in addition to brain imaging, especially in high-risk patients. Previous studies have shown that approximately 50% of patients with non-arteritic CRAO have abnormal echocardiographic findings, indicating an embolic source.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, for low vision categories such as "counting fingers", "hand motion", "light perception" and "no light perception," corresponding logMAR values were determined as 2.0, 2.3, 2.6, and 2.9 respectively 20 . A favorable visual outcome was defined as a significant improvement in visual acuity, characterized by a reduction of 0.3 or more in logMAR 21 .…”
Section: Visual Outcome Measurementmentioning
confidence: 99%